AN OBSERVATIONAL STUDY ON NIDANARTHAKARA ROGA SIDDHANTA W.S.R. TO PRATISHYAYAT SANJAYTE KASA - Parashuram, *Pawar; Sucheta, Pawar; Milind, Aware; Somadatta, Kulkarni; Popat, Jagtap (International Journal of Ayurveda and Pharma Research, 2017)
Nidan (causative factor) plays important role in course and onset of any disease. Many times one disease may become the cause of another disease. The concept is explained by Acharya Charaka under the heading Nidanarthakara Roga. Further he has narrated the examples of Nidanarthakara roga as Pratishyaya, Kasa, Kshaya, Shosha, Udara etc. In day to day practice it is very important to know the Nidanarthakaratwa of any disease. It not only leads to development of another disease but also hampers the immunity of patient also. The present observational study was carried out with the prime aim of assessing Nidanarthakaratwa of Pratishyaya. The study included 60 patients between the age group 16-60 having the clinical sign and symptoms of Kasa. Along with general observations the observations relating previous history of Pratishyaya in Kasa patient were also noted to find out Nidanarthakaratwa of Pratishyaya in Kasa. The detail observations like course, onset and type of Nidan were also noted to find out Nidanarthakaratwa of Pratishyaya in Kasa Vyadhi. It was found that more than 50% patients of Kasa were previously suffered from Pratishyaya which supports the Charakokta Nidanarthakara Roga Siddhant Pratishyayat Sanjayte Kasa. The importance or scope of the present study is to make aware the people about Nidanarthakaratwa of Pratishyaya. Also early intervention is necessary in Pratishyaya and Dushta condition of Pratishyaya should not be neglected.